Pengaruh Sifat Muroqobah Terhadap Etos Kerja Karyawan di Desa Sei Paham - Annisa Umairoh (Medan Resource Center, 2021)
The nature of muroqobah is important in a person, because it becomes self-awareness to be careful at work, feels under the supervision of Allah, gives birth to self-improvement and increases the quality and creativity of work. Of course it will have a good impact on the work ethic and work performance of employees, but if it is not realized properly it will have a bad impact on the quality of self-performance and others. This type of research is a field research using a qualitative approach that produces descriptive data in the form of writing and actions and behaviors that can be observed from the subject. The results showed that the application of muroqobah in work ethic greatly affects the quality and creativity of employee performance.